Hemophagocytic lymphohistiocytosis mimicking neonatal hemochromatosis. (3rd October 2019) - Broglie, Larisa; Vitola, Bernadette; Thakar, Monica S.; Basel, Donald; Szabo, Sara; Agni, Rashmi; Talano, Julie-An
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a potentially fatal illness characterized by impaired natural killer (NK) cell and cytotoxic T-cell function. Patients develop systemic inflammation, multisystem organ dysfunction, and if untreated, death. Patients who present in the neonatal period often have atypical presentations with evidence of liver dysfunction and cholestasis; this has a broad differential diagnosis including neonatal infection, congenital liver defects, or other causes of liver dysfunction, such as neonatal hemochromatosis. Here, we present an infant whose diagnosis of familial HLH was confounded by the history of a stillborn sibling with suspected neonatal hemochromatosis, ultimately delaying diagnosis and initiation of curative treatment. This highlights the need to maintain a low threshold for sending HLH work-up concurrently with evaluation of liver diseases in infants with liver dysfunction, to ensure timely diagnosis and initiation of treatment. Clinicians should maintain a high index of suspicion for HLH and be aware that HLH may mimic the findings on liver biopsy seen in neonatal hemochromatosis.